Culture Goes To War: A Critical Analysisof the Human Terrain System in Iraq and Afghanistan - Dunne, David (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2022)
From 2003 onwards, faced with burgeoning insurgencies and widespread violence in Iraq and Afghanistan, US military policy underwent a cultural turn . This shift in policy emphasised the need for the collection of knowledge of adversary culture in order to effectively prosecute counterinsurgency operations. This emphasis upon the value and importance of cultural knowledge set the stage for the introduction of new, non-military expert knowledge(s) into the field, culminating in the development of the Human Terrain Systems [HTS] programme. HTS deployed social scientists and academics to provide military commanders with accurate socio-cultural knowledge of populations at sites of military intervention. Through critical engagement with the publicly available research produced by HTS and the personal lived experience of former members as recounted in their reflections on their time with the project, this study interrogates the instrumentalization of specific anthropological understandings of culture as technologies of Western military intervention. In exploring the self-understandings of researchers experiences in the field, the study theorizes the commitment demonstrated to the veracity of knowledge produced through the practice of social scientific research, the conceptualisation of the relationship between the researchers and their subjects, and the instrumental nature of the knowledge produced by HTS. The study then explicates the deployment of the concept of tribe during HTS research in Iraq, and analyses arguments put forward regarding the potential of traditional tribal reconciliation mechanisms and tribal governance structures to remedy sectarian violence and stabilize the country. Finally, I examine HTS research conducted in Afghanistan, and explore how critiques informed by new anthropological approaches to the culture concept problematised tribe as a unit of analysis and, in its place, offered alternative generalisable schemas to explain Afghan social organisation. The study demonstrates that HTS discourses in Iraq and Afghanistan are informed by and serve to reproduce a crude binary distinction between an essentialised, primitive, native Other and a rational, progressive, scientific West which is reminiscent of 19th century British colonial discourses of indirect rule. Furthermore, it concludes that the pervasiveness of old anthropological approaches to culture in HTS research is a direct function of its usefulness to the realisation of military objectives in Iraq and Afghanistan. In doing so, this research aims to contribute to a reflexive inversion of the social scientific gaze to account for its complicity in processes of domination and intervention.
APPROVED
Keywords: Human Terrain System, Liberal Intervention, Conflict Studies, Postcolonial Studies, Iraq War, Afghanistan War, War on Terror, Orientalism, War Studies, Culture